1980
DOI: 10.1113/jphysiol.1980.sp013172
|View full text |Cite
|
Sign up to set email alerts
|

Blood—cerebrospinal fluid transfer of plasma proteins during fetal development in the sheep

Abstract: SUMMARY1. The penetration of human and sheep plasma proteins from blood into c.s.f. of sheep fetuses (57-86 days gestation) has been studied. The proteins were injected intravenously via cotyledonary vessels. After different time periods the c.s.f. concentrations of marker proteins were estimated by radioactive counting of iodinated human or sheep proteins or by immunoassay of human proteins.2. Several proteins of similar molecular size penetrated into c.s.f. to a different extent in 60 day fetuses. The steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 27 publications
8
84
1
Order By: Relevance
“…On the other hand, E-CSF has a complex protein composition, and the exposure of the apical surface of neuroepithelial cells to this fluid could affect their behavior (Dziegielewska et al 1980a(Dziegielewska et al , 1980b(Dziegielewska et al , 1981(Dziegielewska et al , 1991(Dziegielewska et al , 2000Checiu et al, 1984;Gato et al, 2004). Experimental data demonstrate that the loss or modification of the composition of the E-CSF strongly decreases the neuronal cell population (Desmond and Jacobson, 1977;Desmond, 1985).…”
Section: E-csf Helps Control Cellular Behavior In Neuroepithelial Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, E-CSF has a complex protein composition, and the exposure of the apical surface of neuroepithelial cells to this fluid could affect their behavior (Dziegielewska et al 1980a(Dziegielewska et al , 1980b(Dziegielewska et al , 1981(Dziegielewska et al , 1991(Dziegielewska et al , 2000Checiu et al, 1984;Gato et al, 2004). Experimental data demonstrate that the loss or modification of the composition of the E-CSF strongly decreases the neuronal cell population (Desmond and Jacobson, 1977;Desmond, 1985).…”
Section: E-csf Helps Control Cellular Behavior In Neuroepithelial Cellsmentioning
confidence: 95%
“…In this way, several studies have demonstrated that, during development, the most prevalent components of the E-CSF are proteins. Moreover, the fact that the protein fraction of the CSF is more complex in embryos than in adults, and that it is detected at higher concentrations, has led some authors to suggest that the E-CSF is involved in the regulation of neuroepithelial cell behavior (Dziegielewska et al, 1980b(Dziegielewska et al, , 2000Ojeda and Piedra, 2000;Miyan et al, 2003;Gato et al, 2004). In addition, it has been shown that E-CSF plays a key role in the expansion of the embryonic brain primordium at the earliest stages of development (Desmond and Jacobson, 1977;Desmond, 1985;Gato et al, 1993;Alonso et al, 1998Alonso et al, , 1999Desmond and Levitan, 2002).…”
mentioning
confidence: 99%
“…Thus in 60-day-old fetal sheep (Dziegielewska et al 1980 b) and in neonatal rats (Habgood, 1990), albumin CSF/plasma ratios are similar to those of inulin, but the molecular radius of albumin is some three times larger than inulin. Also the CSF/plasma ratios for individual proteins are not the same in spite of the fact that their molecular sizes are similar (Dziegielewska, Evans, Fossan, Lorscheider, Malinowska, M0llgard, Reynolds, Saunders & Wilkinson, 1980a;Dziegielewska et al 1980b). It has been noted in earlier experiments on developing sheep brain that different species of the same protein, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the albumin permeability experiments were run for 3 h because previous studies in this preparation had shown that several exogenous proteins including human albumin approached a steady-state level in cisternal CSF by 3-6 h after i.v. injection of the protein solution (Dziegielewska et al 1980b (Fig. 2).…”
Section: Morphological Techniquesmentioning
confidence: 99%
See 1 more Smart Citation